2021
DOI: 10.1101/2021.02.16.21251807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of COVID-19 on long-term health and health care use

Abstract: Aim: To explore impacts of mild and severe COVID-19 on acute and long-term utilization of primary care, inpatient- and outpatient specialist health care. Methods: In all persons tested for the SARS-CoV-2 in Norway March 1st to November 1st 2020 (N=1 257 831), we used a difference-in-differences design to contrast the monthly health care use before and after testing, across patients with negative test (no COVID-19) and 1) positive test, not hospitalized (mild COVID-19) and 2) positive test, hospitalized (severe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Thus, our findings may imply that the severity grade of post-covid complaints are limited for children (no specialist care needed). These findings of limited impact of mild COVID-19 on long-term morbidities in children, are also consistent with our recent findings of limited long-term comorbidities following mild COVID-19 in adults 1 . However, we here show that the elevation of primary care use may last longer for the youngest children (1-5 years) than what we observed for adults using similar methods 1, 18 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, our findings may imply that the severity grade of post-covid complaints are limited for children (no specialist care needed). These findings of limited impact of mild COVID-19 on long-term morbidities in children, are also consistent with our recent findings of limited long-term comorbidities following mild COVID-19 in adults 1 . However, we here show that the elevation of primary care use may last longer for the youngest children (1-5 years) than what we observed for adults using similar methods 1, 18 .…”
Section: Discussionsupporting
confidence: 92%
“…The content, duration and impact of the post-covid syndrome has been described for adults in several studies. We recently showed that adults with severe COVID-19 may experience complaints for up to 3-6 months after initial infection, mainly due to respiratory and circulatory conditions 1 . These findings line up with a range of other reports showing increased risk of complications after serious disease among adults, implying that severe COVID-19 has a considerable impact on long-term health care utilization [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…16,19 Contrary to our findings however, a Norwegian study suggested that mild COVID-19 does not persist to cause a need for healthcare beyond two months following a positive test. 22 It is unclear if symptoms or diseases post-COVID-19 are due to the infection itself, anxiety caused by diagnosis and isolation or due to complications. Whilst this study does not inform us about mechanisms, it further paints the picture, helping us understand the population-level burden of post-COVID-19 sequelae across the spectrum of acute infection severity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we had no comparison group, simply because we did not aim for any causal inference and because comparable data are not available for a similar epidemic or pandemic setting with other infectious diseases. However, in recent studies of post-acute COVID-19, we demonstrate a likely causal effect of being infected with SARS-CoV-2 on the post-acute health care use [14]. Here, we also exclusively included visits that were specific to COVID-19, i.e.…”
Section: Discussionmentioning
confidence: 99%